2017
DOI: 10.3906/kim-1601-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of DNA interaction with Mannich base derivatives by disposable graphite electrodes

Abstract: Four different Mannich base derivatives containing an aromatic/heteroaromatic propanone structure (C1 (3-(dimethylamino)-1-(thiophen-2-yl)propan-1-one hydrochloride); C2 (3-morpholino-1-(pyridin-3-yl)propan-1-one hy-propan-1-one hydrochloride)) were earlier synthesized and characterized with 1 H NMR, 13 C NMR, MS, and elemental analysis. The interaction of these compounds with fish sperm double stranded DNA (fs-dsDNA) was investigated by using differential pulse voltammetry (DPV) in connection with a disposabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Mannich reaction, one of the most familiar C-C bond forming reactions in organic synthesis, provides a suitable method to introduce amino alkyl substituent on the molecule [18]. Recently, Istanbullu et al reported a series of uracil CMannich bases as potent cytotoxic agents [19]. It has been widely accepted that Mannich derivatives have significantly improved activity profile compared to their parent analogues.…”
Section: Chemistrymentioning
confidence: 99%
“…Mannich reaction, one of the most familiar C-C bond forming reactions in organic synthesis, provides a suitable method to introduce amino alkyl substituent on the molecule [18]. Recently, Istanbullu et al reported a series of uracil CMannich bases as potent cytotoxic agents [19]. It has been widely accepted that Mannich derivatives have significantly improved activity profile compared to their parent analogues.…”
Section: Chemistrymentioning
confidence: 99%
“…Similarly, the interaction of DNA with lycorinean alkaloid found in various Amaryllidaceae species has also been reported [8]. Mitoxantrone [9], doxorubicin [10], a series of Mannich bases [11] an imidazoacridinone derivative, Symadex [12] are some of the literature reports based on electrochemical detection of interaction of drugs with DNA.…”
Section: Introductionmentioning
confidence: 95%